Safety of intravenous tobramycin in combination with a variety of anti-pseudomonal antibiotics in children with cystic fibrosis - Deschamp, Ashley R (SAGE Open Med, 2017)
OBJECTIVES: Previous studies have examined renal safety of once daily intravenous tobramycin in individuals with cystic fibrosis. This has been mainly in combination with ceftazidime in an adolescent or adult population. In this report, we describe our institutional experience of once daily intravenous tobramycin in combination with a variety of second anti-pseudomonal antibiotics in children with cystic fibrosis. METHODS: We present a retrospective review including children with cystic fibrosis, who were admitted for a pulmonary exacerbation from January 2009 to December 2011, and treated using intravenous tobramycin. A literature review of once daily intravenous aminoglycoside dosing in cystic fibrosis was performed to compare our results to existing literature. RESULTS: A total of 35 subjects were divided into once daily dosing (n = 20) versus multiple daily dosing (n = 15) groups. Mean age was 11.3 years (± 5.7) for the once daily dosing group and 13.1 years (± 4.4) for the multiple daily dosing group (p = 0.34). All subjects had normal baseline serum creatinine at admission (once daily dosing 0.49 ± 0.14 mg/dL vs multiple daily dosing 0.62 ± 0.23 mg/dL, p = 0.07). All subjects received intravenous tobramycin, and most received piperacillin-tazobactam as their second anti-pseudomonal antibiotic (once daily dosing 45% and multiple daily dosing 40%). There was no significant change in serum creatinine in either group during antibiotic treatment (once daily dosing 0.08 ± 0.12 mg/dL vs. multiple daily dosing 0.06 ± 0.10 mg/dL, p = 0.43). All subjects had significant improvement in lung function following intravenous antibiotic therapy. CONCLUSION: We show that both once daily dosing and multiple daily dosing of intravenous tobramycin in combination with a variety of second anti-pseudomonal antibiotics were safe in terms of nephrotoxicity in children with cystic fibrosis. These findings are important given existing literature mainly examines once daily tobramycin in combination with ceftazidime, a cephalosporin, and the majority of our patients were on tobramycin with piperacillin-tazobactam, an extended spectrum penicillin plus beta-lactam. This contributes new information not previously examined in a pediatric cystic fibrosis population.